Adaptive distance protection for grid-connected wind farms based on optimal quadrilateral characteristics. (July 2021) - George, Sujo P.; Ashok, S.
Highlights: Algorithm which calculates the optimal and adaptive settings of quadrilateral distance relay. Distance relay is made adaptive according to the operating conditions of the wind farm. Mal-operation of distance relays during load encroachment condition is avoided by optimal settings. The proposed algorithm is validated using case studies and experimentation. Abstract: Wind farms are generally connected to a power grid through transmission lines. The length of the transmission line depends on the rated capacity and the location of the wind farms. The fault level of the grid to which the wind farm is connected may change as the source impedance varies based on the number of wind generators (WGs) in service. This study shows that the distance relays in wind-integrated substations with conventional settings mal-operate during fault intervals depending on the operating conditions of the wind farm. The generalized characteristics of the distance relays require modification under such circumstances. In this work, an adaptive protection scheme is proposed to calculate the optimal settings of the quadrilateral distance relays according to variations in wind-power penetration. The algorithm is then validated through case studies in the laboratory using the IEEE 30-bus test system, a typical wind-integrated substation, and an experimental setup. Graphical abstract: Image, graphical abstract